Ocorrência de Frankliniella schultzei (trybom) (thysanoptera: thripidae) em plantas daninhas - Lima, Maria G. A.; Martinelli, Nilza Maria [UNESP]; Monteiro, Renata C. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2000)
Realizaram-se levantamentos de plantas daninhas, no Campus da UNESP em Jaboticabal/SP, com o objetivo de identificar espécies de plantas daninhas hospedeiras do tripes Frankliniella schultzei (Trybom). As plantas foram coletadas semanalmente utilizando-se o método de ensacamento. A separação dos tripes foi feita mediante emprego do funil de Berlese. Entre as 43 espécies de plantas daninhas encontradas nas áreas amostradas, 19 são hospedeiras do tripes. Rabanete (Raphanus sativus L.), nabiça (R. raphanistrum L.) e mostarda (Sinapsis arvensis L.) foram as que apresentaram as maiores porcentagens de F. schultzei, 45, 27 e 17% do total de fêmeas coletadas respectivamente.

A monitoring of weeds was carried out on the UNESP Campus in Jaboticabal, SP, with the objective of indentifying host weed species of Frankliniella schultzei (Trybom). The plants were collected weekly and transported to the laboratory inside paper bags. The Berlese funnel method was used to separate the insects from the plants. Thrips were found in 19 of the 43 weed species studied: Raphanus sativus L., R. raphanistrum L., and Sinapsis arvensis L. presented the highest percentage of thrips, consisting of 45, 27, and 17% respectively of the total females that were collected.
Ocurrence of Frankliniella schultzei (Trybom) (Thysanoptera:Thripidae) at weed species
Keywords: Insecta; Host plant; Thrips; toposvirus; vector; Insecta; Tripes; hospedeiros; tospovírus; vetor